Factors Related to C-Section Delivery at YK Madira RSU Palembang 2021 - Narzuyah Narzuyah; Satra Yunola; Eka Afrika (Science Midwifery, 2022)
Based on the results of the Basic Health Research (Riskesdas) in 2018, the incidence of sectio caesarea in Indonesia was 17.6%, the highest in the DKI Jakarta area at 31.3% and the lowest in Papua at 6.7% (KEMENKES RI, 2019). Based on data at RSU YK Madira Palembang the number of deliveries in 2018 was 1353, the caesarean section rate was 42.36%, the 2019 delivery rate was 1207 while the cesarean section was 44.3%, the 2020 delivery rate was 1,209 while the cesarean section rate was 55, 7%. The data used in this study is secondary data sourced from medical records at YK Madira Hospital Palembang. This type of research is quantitative research using the Analytical Survey research method, the data collection technique is not directly addressed to the subject. This research was conducted by cross sectional. The population in this study were 1209 mothers who gave birth with a total sample of 92 people. The results showed that the results of the Chi-square statistical test on age (0.003), parity (0.024), and history of cesarean section (0.000) < (0.05). The conclusion of this study is that there is a relationship between parity age and history of cesarean section with caesarean section delivery at YK Madira Hospital Palembang in 2021.